Radiotherapy for Thymic Carcinoma: Adjuvant, Inductive, and Definitive - Komaki, Ritsuko; Gomez, Daniel (Frontiers in Oncology, 2014)
Although historically thymoma and thymic carcinoma have been treated surgically, radiation therapy also has an important role, either as postoperative therapy to reduce the risk of mediastinal recurrence or as part of definitive treatment for patients who cannot undergo surgery. Induction chemotherapy and molecular targeted agents may also be appropriate for thymic carcinoma, the behavior of which resembles non-small cell lung carcinoma more than that of thymoma or invasive thymoma and is increasingly being treated like lung cancer. We present here a review of current therapies for thymic malignancies and briefly discuss the potential benefits from novel technologies for such treatment.